Variabilitas Strain-Strain PStV pada Tingkat Molekul Berdasarkan Gen Protein Selubung dan 3' UTR (Untranslated Region) Genom RNA PStV - Hasriadi Mat Akin; Sudarsono Sudarsono (Universitas Gadjah Mada, 2002)
Variability of various peanut stripe virus (PStV) strains at the molecular level was studied based on nucleotide sequence of coat protein (CP) cistron and 3' UTR (untranslated region). Six PStV strains causing different types of symptoms on peanut leaves (Arachis hypogaea var. Landak) were used in this study. Fourteen point mutations on the coat protein gene have been identified among the PStV strains, however, only two point mutations at three positions (9309 of PStV-lsb and PStV-lbs and 9885 of PStV-Ibs) resulted in amino acid residue changed of the coat protein. Pair comparison among six 3' UTR sequences of the strains revealed a 97.9 - 100% sequence similarity. The results provided evidence that all the strains were of the same virus and there is no correlation between typical symptoms of the PStV infection and CP sequence variability among the strains.